Assessing the impact of end‐member selection on the accuracy of satellite‐based spatial variability models for actual evapotranspiration estimation. Issue 5 (28th May 2013) - Long, Di; Singh, Vijay P.
Key Points Endmembers largely determine the magnitudes of EF retrievals Endmembers have minor effect on standard deviation and skewness of EF retrievals Predictability of ET models depends mostly on the ability of Ts to capture EF